Effects of high-power pain threshold ultrasound technique in patients with knee osteoarthritis: A single-blind randomized controlled trial - Yomna F. Ahmed; Rania M. Tawfik; Ahmed M. Tawfick; Shimaa T. Abu El Kasem (Sport TK, 2023)
Osteoarthritis (OA) is a highly prevalent, degenerative disease of the joints manifested by joint pain, tenderness, decreased function, and limited range of motion (ROM). The current study aimed at evaluating the therapeutic effect of the high-power pain-threshold ultrasound technique (HPPTUS) in comparison with conventional ultrasound (US) techniques in patients with knee osteoarthritis (KOA). A single-masked, pre–post randomized controlled trial was conducted. Fifty participants of both sexes (between 40 and 50 years of age), diagnosed with stage II knee osteoarthritis, participated in this study. They were randomized into two groups: Group A (experimental group, n=25), which received HPPTUS on the knee joint in addition to the traditional treatment (hot packs and isometric exercise for quadriceps), and Group B (control group, n=25), which received conventional ultrasound on knee joint in addition to the traditional treatment (hot packs and isometric exercise for quadriceps). Both groups underwent a four-week treatment plan in which sessions were conducted twice per week. The visual analogue scale (VAS) was used to estimate the intensity of pain, Digital Electronic Pressure Algometer was used to measure pressure pain threshold (PPT) on trigger point around knee, and Digital goniometer was utilized to assess ROM of the knee joint before and after treatment. The MANOVA test revealed statistically significant improvements in all variables (VAS, PPT, knee ROM) post-treatment compared to pre-treatment values in the HPPTUS group (experimental group) (p < 0.05), while the control group revealed statistically significant improvement only in VAS post-treatment compared with pre-treatment (p < 0.05). Comparison between groups revealed statistically significant improvements in VAS, PPT, knee ROM in participants receiving HPPTUS compared with the control group (p < 0.05). High-power ultrasound can be effectively implemented in the treatment of knee OA as it produces significant improvements in the intensity of pain, pressure-pain threshold, and knee joint ROM.